Drive in Sports: How Mental Fatigue Affects Endurance Performance - Schiphof-Godart, Lieke; Roelands, Bart; Hettinga, Florentina J. (Frontiers in Psychology, 2018)
Performance in endurance sports relies on athletes’ drive, which is the sum of all factors pushing athletes to exert effort during exercise. Mental fatigue can influence endurance performance by decreasing athletes’ drive to exercise. From a psychological point of view, mental fatigue has two separate components: it can affect drive by increasing the perceived effort necessary for a given task (“I cannot do this, I am too exhausted”), or by decreasing the perceived value of the reward that can be obtained (“I do not want to do this, it is not worth it”). Neurophysiological theories confirm this dual nature of mental fatigue. Mental fatigue can activate the inhibition centers of the brain, increasing perceived effort for a task, hence decreasing drive and willingness to act. On the other hand, it may also deactivate facilitative brain centers (normally responsible for motivated behaviour and increased drive towards a reward), also resulting in decreased drive. In this Perspective we will adopt a multidimensional approach, describing how mental fatigue interacts with drive and performance in endurance exercise. We will study the interaction between mental fatigue and other factors impacting on drive, such as perceived exertion and motivation, and examine how these factors combined result in athletes’ exercise behaviour (such as pacing) and performance. This will provide researchers, coaches and athletes with useful tools in order to understand, influence and enhance athletes’ drive in exercise, which is of high relevance in elite endurance sports, where mental fatigue, motivation and stakes are of Olympic level.